Food Security Analysis of Corn Farming Households In The Buffer Area of Mandalika Special Economic Zone - Hidayati, Asri; Septiadi, Dudi; Usman, Abdullah; Hidayanti, Anna Apriana (PT. Riset Press International, 2024)
The existence of the Mandalika Special Economic Zone (SEZ), located in Pujut District, Central Lombok Regency, is an area adjacent to many corn cultivation areas. This condition represents strategic potential for the development of corn commodities and their derivative products. On the other hand, food security is a human right that must be fulfilled. The aim of this research is to; 1) Analyze the socio-economic conditions of corn farmers in the buffer area of Mandalika SEZ; 2) Analyze the food security of corn farmers houshold in the buffer area of Mandalika SEZ; This research was conducted using qualitative-descriptive methods. The data collection technique used interviews with respondents guided by a questionnaire with 40 respondents determined by simple random sampling. The data analysis that will be used in this research is descriptif analysis. The research results show that (1) the average total income of corn farmers is IDR. 28,960,605.28/year, this income comes from agricultural activities amounting to IDR. 23,430,722.93/year, income from non-agricultural activities of IDR. 4,164,000/year and income from other sources (Social-Assistance) of IDR. 1,365,882/year. The average total household expenditure for corn farmers is IDR. 19,506,628/year, with details of food expenditure of IDR. 11,169,548/year, and non-food expenditure of IDR. 8,337,080/year; (2) In general, respondent farmer households included the food secure category. In distribution, there are 20% of farmers who are still in the food insecure category.